SPREADING THE UNDERSTANDING OF WOMEN'S IDENTITY WITHIN THE METO CULTURE THROUGH THE CHRISTIAN EDUCATION SPACE USING THE CONTEXTUAL TEACHING AND LEARNING MODEL - Hale, Merensiana (QUAERENS: Journal of Theology and Christianity Studies, 2024)
Women in Meto culture have a uniqueness that can only be understood if they understand the construction of Meto culture. In general, many people always associate women's issues with patriarchal culture whose assumptions are oppressive and unfair to women. Women are often seen as marginalized. This paper aims to build a new understanding of women's identity in Meto culture that is more positive in patriarchal culture. There are discussions of women's identity in the Meto culture and its approach through Christian education. This positive understanding is then formed in dialogue with the appropriate biblical texts. Furthermore, the process of seeding this understanding can be carried out in the Christian education space with the Contextual Teaching and Learning learning model. This research was carried out using a literature study that is relevant to the issue of women’s identity in the Meto culture and the results found as content in the Christian education space are that the identity of women in the Meto culture is unique, relational, collective, and cosmic.